2017
DOI: 10.1007/s10661-017-6139-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of tile drainage contribution to streamflow and nutrient loads at the watershed scale based on continuously monitored data

Abstract: Nitrogen losses from artificially drained watersheds degrade water quality at local and regional scales. In this study, we used an end-member mixing analysis (EMMA) together with high temporal resolution water quality and streamflow data collected in the 122 km Otter Creek watershed located in northeast Iowa. We estimated the contribution of three end-members (groundwater, tile drainage, and quick flow) to streamflow and nitrogen loads and tested several combinations of possible nitrate concentrations for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 41 publications
2
31
1
1
Order By: Relevance
“…Lowest NO3-N concentrations were observed in August for all reaches except the Middle Cedar. Our data suggest either more in-stream processing of NO3-N is occurring in the warm water condition of August, or dilution by lower-NO3-N groundwater is disproportionately larger during that time, or both, consistent with existing literature [8,23,25]. Our data also demonstrate that a fixed-location study based in the uppermost 60 km of either stream would show little seasonal variation (Figures 7 and 8).…”
Section: Normalized Concentration Patternssupporting
confidence: 89%
See 4 more Smart Citations
“…Lowest NO3-N concentrations were observed in August for all reaches except the Middle Cedar. Our data suggest either more in-stream processing of NO3-N is occurring in the warm water condition of August, or dilution by lower-NO3-N groundwater is disproportionately larger during that time, or both, consistent with existing literature [8,23,25]. Our data also demonstrate that a fixed-location study based in the uppermost 60 km of either stream would show little seasonal variation (Figures 7 and 8).…”
Section: Normalized Concentration Patternssupporting
confidence: 89%
“…Concentration declines were observed in the Cedar River despite the absence of major tributaries from 325 km-305 km and 180 km-0 km, indicating in-stream processes were likely consuming the nitrogen. Whereas other fixed-location monitoring studies have reported lower NO3-N concentrations in August compared to May, June, and July [8,23,25], our boat-deployed longitudinal analysis showed how these relationships evolve over long reaches from month to month in the growing season. Lowest NO3-N concentrations were observed in August for all reaches except the Middle Cedar.…”
Section: Normalized Concentration Patternscontrasting
confidence: 83%
See 3 more Smart Citations